Educating Homo Oeconomicus? "The Disadvantages of a Commercial Spirit" for the Realization of Democracy and Education. Issue 1 (April 2016) - Stengel, Barbara S.
Abstract: At present, the structures, practice, and discourse of schooling are anchored to a "commercial spirit" that understands students, educators, and parents as economic operators trading competitively in human capital and to a discourse of failure that is disabling those who seek to understand and enact John Dewey's notion of education as democratic practice. Here Barbara Stengel illustrates both the commercial spirit in public schools and the discourse of school failure across two geopolitical settings: Shanghai, China, and urban U.S. schools. She argues that framing the educational enterprise in terms of economic success and failure makes it difficult for educators to address Dewey's vision of democracy and education substantively. Stengel concludes with an acknowledgment that, regardless of putative political commitments, these two public school systems are schooling — though not often educating — the same neoliberal subject, but that Dewey's vision of democracy and education nonetheless remains critical and compelling.